Território em mutação: a implantação de central geradora eólica em Sergipe - Costa, Vanessa Santos (2013)
The energetic sector is one of the areas that more contribute for the increase of the environment degradation, mainly concerning to burning of fossil fuel since they are extreme polluters. This way, the preoccupation with the environment made man to turn to nature searching for in its elements energetic alternatives that could be able to provide energy to sustain his social and technologic development. In this context, we focused our analyse on one of the energetic alternatives that comes from replaceable and natural resources, the eolian energy, since it is a new clear source of energy that aims at reducing these problems. In Sergipe State, with the purpose of contributing for the environment preservation and increasing the energetic matrix of our country, it has being implanted, in the county of Barra dos Coqueiros its first eolian central generator. This project brings the installation of 23 windmills and they will have the capability of producing 35, 6 MW of energy. This location was chosen due to the environment conditions, as the climate and alleviation that are favorable to the project development. Thus, this present study refers to the analyze of the first wind farm implanted in the State and it aimed at learning the general perception of the social authors involved in the process, such as the surrounding population, the government and the responsible enterprise. The methodology began by the bibliographic surveys and visitation in both public and private agencies, field work with application of questionnaires and interviews, during the period of April and July, 2012. With this study it could be observed that the arrival of this enterprise provoked changes in the location landscapes caused by the windmill installations as well as daily life changing of the surrounding people. We searched to comprehend the perception of the main three segments involved referring to eolian energy as a sustainable energy source as well as the conformation of new territories. Government agencies and the involved enterprises in the wind farm implantation translate preocupation with the observance of the legislation, but, specially, with the participation in the magnification and diversification of the energetic matrix of both the State and Country. The majority of the surrounding inhabitants and the head office residents of the county, in turn, show themselves inadvertent or ignore that it does not mean only. a landscape change, but a production of a territory that will affect the neighbor relationship, the access, the values of the real estates, ultimately, the material and symbolic basis that until now remained in their quotidian.